Pre-service Teachers’ Responses to Peer Spoken Feedback in Micro Teaching Class - Krismalita Sekar Diasti (Universitas Sembilanbelas November Kolaka, 2020)
Feedback has been investigating for many years. Previous studies have proved that feedback is a powerful tool which teacher can use to foster students’ achievement. Students can obtain feedback from their peers, teachers, or themselves as a reflection. Feedback can be given through different mode, namely, written or spoken. This survey research aims to examine pre-service teachers’ responses to peer spoken feedback in micro teaching class. This research was conducted in Micro Teaching class F at English Language and Education Study Program of Sanata Dharma University. There were twenty-three participants in this study. Questionnaire and interview were used to gather the data. Based on the findings, the students have positive response towards the use of peer spoken feedback in micro teaching class. The students’ positive response can be seen from their attitude and motivation. The students have positive attitude to the use of peer spoken feedback. They were pleased in the peer spoken feedback activity. The students willing to engage in the activity of peer spoken feedback as well. The students showed the desired response. Through attainning peer spoken feedback, the students became more well-prapared in the teaching practice. Moreover, the students were motivated to perform a better teaching perfromance in the next teaching practice. Key Words: micro teaching, peer spoken feedback, response